2016
DOI: 10.1016/j.margeo.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Geologic records of Holocene typhoon strikes on the Gulf of Thailand coast

Abstract: 8Eric Simon, University of North Texas. 9 10 Washover sedimentation resulting from modern typhoon strikes on the Gulf of Thailand coast 11 forms anomalous sand layers in low-energy coastal environments including marshes, ponds and 12 swales. The primary diagnostic for recognizing prehistoric typhoon-deposited sand layers in the 13 geologic record are sharp upper and lower contacts between coarser-grained transported sand 14 layers and finer-grained in-situ sediments. In this first paleotempestology study in Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 60 publications
2
40
0
Order By: Relevance
“…As the eastern United States is frequently struck by summer hurricanes, researchers tried to understand how the cyclonic season is correlated with global oceanatmosphere mechanisms. Although only a few studies have focused on this recent issue, storminess reconstructions have also been developed for all other continents: Oceania (May et al, 2015(May et al, , 2017Nott and Hayne, 2001), Asia (Lallemand et al, 2015;Liu et al, 2001;Williams et al, 2015;Yu et al, 2009), Africa (Bozzano et al, 2002), South America (Oliveira et al, 2014;Ramírez-Herrera et al, 2012) and Mediterranean coasts (Degeai et al, 2015;Dezileau et al, 2011Dezileau et al, , 2016Kaniewski et al, 2016;Sabatier et al, 2008Sabatier et al, , 2012Vallve and Martin-Vide, 1998). Few studies have investigated the European Atlantic coast, where stormy chronologies are mainly concentrated on the British Isles (Hansom and Hall, 2009;Oldfield et al, 2010;Orme et al, 2015Orme et al, , 2016, and where some other works have recently analyzed Holocene French storms (Sorrel et al, 2009(Sorrel et al, , 2012Van Vliet Lanoe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As the eastern United States is frequently struck by summer hurricanes, researchers tried to understand how the cyclonic season is correlated with global oceanatmosphere mechanisms. Although only a few studies have focused on this recent issue, storminess reconstructions have also been developed for all other continents: Oceania (May et al, 2015(May et al, , 2017Nott and Hayne, 2001), Asia (Lallemand et al, 2015;Liu et al, 2001;Williams et al, 2015;Yu et al, 2009), Africa (Bozzano et al, 2002), South America (Oliveira et al, 2014;Ramírez-Herrera et al, 2012) and Mediterranean coasts (Degeai et al, 2015;Dezileau et al, 2011Dezileau et al, , 2016Kaniewski et al, 2016;Sabatier et al, 2008Sabatier et al, , 2012Vallve and Martin-Vide, 1998). Few studies have investigated the European Atlantic coast, where stormy chronologies are mainly concentrated on the British Isles (Hansom and Hall, 2009;Oldfield et al, 2010;Orme et al, 2015Orme et al, , 2016, and where some other works have recently analyzed Holocene French storms (Sorrel et al, 2009(Sorrel et al, , 2012Van Vliet Lanoe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is likely that the site of core DSR09 in southern Korea (this study) and Kamikoshiki Island in southwestern Japan (Woodruff et al, 2009) were influenced by typhoons with recurving tracks to Korea and Japan during the periods of increased ENSO activity (El Niño–like stage), whereas Thailand coasts (Williams et al, 2016) and Taiwan (Chen et al, 2012) were influenced by typhoons with a westerly path toward south China during the periods of decreased ENSO activity (La Niña–like stage), as suggested by Elsner and Liu (2003). Thus, this study supports the results from Elsner and Liu (2003) and Woodruff et al (2009) suggesting that ENSO activity has potentially played a key role in governing typhoon variability in East Asia.…”
Section: Discussionmentioning
confidence: 82%
“…For example, during the period of 3600–2500 cal yr BP, the typhoon-induced deposition of coarser grain-size sediment in the Kamikoshiki coastal lake corresponded to increased ENSO activity. Recently, Williams et al (2016) traced past typhoon activity on the Gulf of Thailand coast based on typhoon-deposited sand layers and found that a possible oscillating pattern in tropical cyclone activity in the western North Pacific. Their data clearly showed significantly reduced tropical cyclones in Thailand during periods of enhanced ENSO activity ca.…”
Section: Discussionmentioning
confidence: 99%
“…P. Donnelly et al, 2004;Donnelly and Woodruff, 2007;Lambert et al, 2008;Noren et al, 2002;Parris et al, 2009;Scileppi and Donnelly, 2007;Scott et al, 2003) was the first place where this characteristic method significantly developed in the early 21st century. It was then expanded worldwide with some notable examples of works in Oceania (Hayne and Chappell, 2001;May et al, 2016May et al, , 2015Nott et al, 2009;Nott and Hayne, 2001) ; Asia (Liu et al, 2001;Williams et al, 2015;Woodruff et al, 2009;Yu et al, 2009) ; Africa (Bozzano et al, 2002;Khalfaoui et al, 2019) ; in the North Sea (Chang et al, 2006;Jong et al, 2006) ; or in South America (Oliveira et al, 2014;Ramírez-Herrera et al, 2012). In western Europe, several studies have analyzed "cliff top storm deposits" (e.g.…”
Section: State Of Art Of Methodological Approaches To Detect Past Stomentioning
confidence: 99%